The Vibrio fischeri luminescence gene activator LuxR is a membrane-associated protein. - Kolibachuk, D (1993)
The Vibrio fischeri luminescence (lux) genes are activated at sufficiently high culture densities by the transcriptional activator LuxR in combination with a diffusible signal compound termed autoinducer. We have used antibodies directed against LuxR in immunoprecipitation experiments to study the subcellular location of this transcription factor. The LuxR polypeptide was detected in membranes and not in the soluble pool of cytoplasmic proteins from V. fischeri. LuxR was not released from the membranes by 0.6 M KCl or by the nonionic detergents Nonidet P-40, N-octyl-beta-D-glucopyranoside, and Triton X-100. LuxR and a number of other V. fischeri proteins were released from the membranes by EDTA. The autoinducer had no detectable influence on the subcellular location of LuxR. In spheroplasts, neither the abundance nor the molecular mass of the LuxR antigen was influenced by treatment with proteinase K. Together with other information, these results indicate that LuxR is an amphipathic protein that is associated with the cytoplasmic membrane of V. fischeri.